Effectiveness of Web-Based Tailored Advice on Parents' Child Safety Behaviors: Randomized Controlled Trial - van Beelen, Mirjam Elisabeth Johanna; Beirens, Tinneke Monique Jozef; den Hertog, Paul; van Beeck, Eduard Ferdinand; Raat, Hein (JMIR Publications, 2014)
BackgroundInjuries at home are a major cause of death, disability, and loss of quality of life among young children. Despite current safety education, required safety behavior of parents is often lacking. To prevent various childhood disorders, the application of Web-based tools has increased the effectiveness of health promotion efforts. Therefore, an intervention with Web-based, tailored, safety advice combined with personal counseling (E-Health4Uth home safety) was developed and applied. ObjectiveTo evaluate the effect of E-Health4Uth home safety on parents' safety behaviors with regard to the prevention of falls, poisoning, drowning, and burns. MethodsA randomized controlled trial was conducted (2009-2011) among parents visiting well-baby clinics in the Netherlands. Parents were randomly assigned to the intervention group (E-Health4Uth home safety intervention) or to the control condition consisting of usual care. Parents in the intervention condition completed a Web-based safety behavior assessment questionnaire; the resulting tailored safety advice was discussed with their child health care professional at a well-baby visit (age approximately 11 months). Parents in the control condition received counseling using generic safety information leaflets at this well-baby visit. Parents' child safety behaviors were derived from self-report questionnaires at baseline (age 7 months) and at follow-up (age 17 months). Each specific safety behavior was classified as safe/unsafe and a total risk score was calculated. Logistic and linear regression analyses were used to reveal differences in safety behavior between the intervention and the control condition at follow-up. ResultsA total of 1292 parents (response rate 44.79%) were analyzed. At follow-up, parents in the intervention condition (n=643) showed significantly less unsafe behavior compared to parents in the control condition (n=649): top of staircase (23.91% vs 32.19%; OR 0.65, 95% CI 0.50-0.85); bottom of staircase (63.53% vs 71.94%; OR 0.69, 95% CI 0.53-0.88); top and bottom of staircase (68.94% vs 78.28%; OR 0.62, 95% CI 0.48-0.81); storage of cleaning products (30.33% vs 39.91%; OR 0.67, 95% CI 0.53-0.85); bathing of the child (23.46% vs 32.25%; OR 0.65, 95% CI 0.51-0.84); drinking hot fluids (34.84% vs 41.73%; OR 0.76, 95% CI 0.61-0.96); using rear hotplates (79.34% vs 85.27%; OR 0.67, 95% CI 0.50-0.90); and the total risk score in which a higher score indicates more unsafe behavior (mean 13.63, SD 6.12 vs mean 15.34, SD 6.07; beta -1.59, 95% CI -2.26 to -0.93). There were no significant differences for other specific behaviors between the two study conditions. ConclusionsCompared to generic written materials, the E-Health4Uth home safety intervention seems more effective in promoting parents' safety behavior for safe staircases, storage of cleaning products, bathing, drinking hot fluids, and cooking. This study supports the application of Web-based, tailored, safety advice for the prevention of unintentional injuries in the youth health care setting. Trial RegistrationNederlands Trial Register: NTR1836; http://www.trialregister.nl/trialreg/admin/rctview.asp?TC=1836 (Archived by WebCite at http://www.webcitation.org/6MPIGQxpx).